Perkembangan Pertumbuhan Tegakan Setelah Penebangan di Areal IUPHHK-HA PT. Diamond Raya Timber - Istomo Istomo; Mega Damayanti (Jurnal Silvikultur Tropika, 2020)
Peat swamp forest management which is less precise will cause diversity on peat swamp forest decreased, in particular endemic species that can only be grown on peat swamp forest. So the research about the condition of peat swamp forest after logging needs to be done. This research aims to analyze species diversity and the development of stand growth after logging as well as analyze stability of species diversity in logged forest IUPHHK-HA PT Diamond Raya Timber. The data collected by combination of path method and grid line method. This research located in biodiversity strip (Protected Area) and logged over area (LOA) 2013, logged over area (LOA) 2015 and logged over area (LOA) 2016. The results showed that condition of the forest in the studied area was already quite stable with index of evenness ranged at 0.56-0.94. There is decreasin stand potential compared with biodiversity strip areal. Stand potential in biodiversity was 254,06 m3/ha, LOA 2013 was 99,72 m3/ha, LOA 2015 was 53,57 m3/ha and LOA 2016 was 58,41 m3/ha. Keywords: peat swamp forest, stability, stand potential, LOA, diversity